The Political Economy of Commitment to Policies - Josse Delfgaauw; Otto H. Swank (Tinbergen Institute, 2023)
IPCC (2022) documents a looming gap between climate goals and implemented policies and points to a lack of political commitment. We study policymakers' incentives to commit. A policymaker decides on a policy to encourage citizens to make investments and determines the degree of flexibility to change the policy after investments have been made. This adds redistributive concerns to the trade-off between commitment and flexibility. When a majority of citizens invest, redistributive concerns alleviate the time-inconsistency problem. When a minority of citizens invest, redistributive concerns aggravate the time-inconsistency problem. Then, the policymaker either commits too strongly or refrains from commitment altogether.
Keywords: D72; D78; H23; Q52; 330; commitment; flexibility; redistribution; median voter; climate